Factors for High Yields of Autumn Wheat in the Fergana Valley - Azimov Mukhiddinjon Mansurovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The key factors in cultivating autumn wheat and increasing its productivity. Based on recommendations from scientists, the experience of skilled farmers, and the results of advanced grain-producing farms, the implementation of key agrotechnical measures is advised to enhance yield.